Improving the nutritional and livelihood security of landless laborer through the Backyard Farming System - Sahoo, Lopamudra; Kandpal, Basant Kumar; Das, Anup; Debnath, Chandan; Singh, Vinay; Devi, Hiangmayum Lembisana; Bharati, Huirem; Parhi, Janmejay; Singha, Abhijit; Datta, Joydeep; Das, Biswajit; Mishra, Vinay Kumar (Frontiers in Sustainable Food Systems, 2023)
Introduction India is home to around 140 million landless laborers who live below the poverty line and are the most vulnerable group in terms of food and nutritional security. The three critical problems faced by the poor laborer families are poverty, hunger, and malnutrition. To address these problems, a backyard farming system was conceptualized and evaluated with an aim to ensure the nutritional security of landless laborers. The main objective of this work was to utilize the homestead area of 100-150 m2 for ensuring year-round food availability. Methods Integration of vegetables, pulses, fruits, spices, fishes, and ducks was done in the available area. Technological interventions with the integration of ducks (Khaki campbell), fish (carps and Self-recruiting species), pulses, and leafy vegetables can help in improving nutrient consumption. Result and discussion A total of 1400 kg of vegetables (including root vegetables and leafy vegetables) can be produced annually from an area of 150 m2 that can fulfil 30-70% of the vitamins (RDA of 70 % of B1 and 30% of B3) and mineral requirements (RDA of 45% of Iron and 30% of Ca) of the average family, as well as providing an annual saving of INR 25,000/annum and an extra income of INR 10,000/annum that can be earned from selling the extra produce. Herbs (Coriander, Mint, and Fenugreek) and spices (Ginger, Turmeric, and Chilli) with antioxidants ranging from 2-13 millimol/100 gm can help in developing a good immune status. Integration with ducks, pond dyke utilization with cucurbits, spices and herbs, and the introduction of self-recruiting species in a composite fish culture system can further enhance the income by INR 14,000/annum after family consumption. Year-round cultivation made the optimum use of the available resources. A net return of INR 30,000 from 300 m2 could be obtained with a B:C ratio of 2.98 as well as generating an employment of 136 mandays. The food produced from the system can contribute to the nutritive requirements throughout the year and lead to a greater diversity in the food consumption pattern of the family.